ALMS1 Regulates TGF-β Signaling and Morphology of Primary Cilia - Álvarez-Satta, María; Lago-Docampo, Mauro; Bea-Mascato, Brais; Solarat, Carlos; Castro-Sánchez, Sheila; Christensen, Søren T.; Valverde, Diana (Frontiers in Cell and Developmental Biology, 2021)
In this study, we aimed to evaluate the role of ALMS1 in the morphology of primary cilia and regulation of cellular signaling using a knockdown model of the hTERT-RPE1 cell line. ALMS1 depletion resulted in the formation of longer cilia, which often displayed altered morphology as evidenced by extensive twisting and bending of the axoneme. TGF-β/BMP signaling, which is regulated by primary cilia, was similarly affected by ALMS1 depletion as judged by reduced levels of TGFβ-1-mediated activation of SMAD2/3. These results provide novel information on the role of ALMS1 in the function of primary cilia and processing of cellular signaling, which when aberrantly regulated may underlie Alström syndrome.